The Connection Between Pareto Optimality and Portfolio Growth Rate - Rentsen, Enkhbat; Ganlkhagva, Gantigmaa (Journal of Institute of Mathematics and Digital Technology, 2022)
Portfolio optimization plays an important role in investment sciences. We examine the classical Markowitz model from a viewpoint of Pareto optimality. We consider a multi-objective optimization problem by maximizing the return of a portfolio and minimizing risk. We show that for appropriate weights, the Pareto optimal solution of the multi-objective optimization is a solution to the problem of maximizing a portfolio growth rate. Numerical results were provided using Mathlab. Багцын Өгөөжийн Өсөлт ба Парето Оновчлол Хураангуй: Хөрөнгө оруулалтын шинжлэх ухаанд багцын оновчлол чухал үүрэг гүйцэтгэдэг. Бид энэхүү ажилд Марковицын сонгодог загварыг Паретогийн оновчлолтой холбон, багцын өгөөжийг нэмэгдүүлэх, эрсдлийг багасгахын тулд олон зорилтот оновчлолын бодлогыг авч үзлээ. Олон зорилтот оновчлолын Парето шийдүүд нь багцын хамгийн их өсөлтийг тодорхойлох асуудалд хариу өгдөг гэдгийг бид харууллаа. Тоон үр дүнг Матлаб ашиглан гаргасан. Түлхүүр үгс: Марковицийн онол, Олон-зорилтот оптимизаци